TRACING THE NATION'S IDENTITY THROUGH THE DIVERSITY OF CONTENT AND LANGUAGE OF ANCIENT MANUSCRIPTS OF SUMEDANG LARANG PALACE - Daffa, Muhammad; Nurmutia, Syahreen (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACT The present study examines the exploration of national identity, as reflected in the diverse content and linguistic aspects of the historic manuscripts housed in the Sumedang Larang Palace. The investigation emphasizes previously unexplored facets of these manuscripts. The research design employed is qualitative in nature, with a case study approach offering an in-depth understanding of the subject matter. The data collection included both primary and secondary sources. Field data served as the primary source of information, and secondary data was obtained from literary sources, thereby providing a comprehensive perspective. Data was analyzed through the stages of inventory, classification, and interpretation. The results of this study significantly enhance the understanding and preservation of cultural heritage, thereby serving the interests of both present and future generations. The analysis reveals a rich diversity in content and language within the manuscripts, showcasing a unique blend of collaboration and acculturation of religious values that have shaped the cultural identity. Moreover, this study affirms that these manuscripts are imbued with religious teachings and cultural values that contribute substantially to the formation of national identity, in alignment with the principles of Pancasila. The intellectual contributions drawn from these manuscripts are deeply rooted in religious and cultural values, leaving a substantial legacy for future scholarship. In conclusion, this research underscores that the ancient manuscripts of the Sumedang Larang Palace are a testament to the perpetuation of religious and cultural traditions, which form an integral part of the Indonesian national identity. Keywords: Culture, Manuscript, Religion, Sumedang Larang ABSTRAK Penelitian ini membahas tentang pencarian identitas nasional melalui keragaman isi dan bahasa naskah kuno Keraton Sumedang Larang, dengan fokus pada aspek-aspek yang belum pernah diketahui sebelumnya. Melalui studi kasus, jenis penelitian yang digunakan adalah kualitatif. Data kualitatif dikumpulkan dari sumber primer dan sekunder. Data lapangan merupakan data primer, sedangkan data kepustakaan merupakan data sekunder. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dan kemudian dianalisis melalui tahap inventarisasi, klasifikasi, dan interpretasi. Temuan penelitian ini memberikan kontribusi yang signifikan terhadap pelestarian dan pemanfaatan warisan budaya untuk kepentingan generasi sekarang dan yang akan datang. Terbukti dari temuan keragaman isi dan bahasa yang digunakan dalam naskah, berbagai naskah merupakan bentuk kolaborasi dan akulturasi yang tulus dengan nilai-nilai agama sehingga membentuk sebuah identitas budaya. Penelitian ini juga membuktikan bahwa berbagai naskah mengandung ajaran agama dan nilai-nilai budaya yang berkontribusi dalam membangun identitas nasional yang sejalan dengan Pancasila. Sumbangan pemikiran melalui naskah-naskah yang ditemukan memiliki makna yang dilandasi oleh nilai-nilai agama dan budaya yang meninggalkan warisan keilmuan bagi generasi mendatang. Penelitian ini menegaskan bahwa naskah-naskah kuno yang diteliti di Keraton Larang Sumedang merupakan kelanjutan dari tradisi agama dan budaya yang menjadi jati diri bangsa Indonesia. Kata kunci: Agama, Budaya, Manuskrip, Sumedang Larang